The Influence of Using the Murottal Method in Improving the Reading of Mad Laws in Surah Ar-Rahman - Maudin; Muhamad Ridwan; Rusli; Basri (AIQU: Journal Multidiscipliner of Science, 2025)
This study investigates the effect of the murottal method on improving fifth-grade students’ understanding of madd rules in Surah Ar-Raḥman at SDN 3 Katobengke. Madd rules constitute an essential component of tajwid and require auditory sensitivity and consistent practice to distinguish correct elongation length in Qur’anic recitation. A quantitative approach with a quasi-experimental one-group pretest–posttest design was employed. The participants were 28 students from Grade 5 selected through total sampling. Data were collected using test and non-test techniques. Test instruments included a written pretest and posttest assessing students’ ability to identify madd locations, classify madd types, and determine appropriate elongation length, as well as an oral recitation performance test evaluated with an analytic rubric measuring accuracy of madd duration, fluency, and tempo consistency. Non-test data were gathered through classroom observation sheets documenting instructional implementation and student engagement, supported by recitation recordings as documentation. Data analysis involved descriptive statistics and inferential testing using a paired-samples t-test, preceded by assumption checks for normality. Learning improvement was also examined using N-gain to categorize individual progress. The results indicate a significant increase in students’ written test scores and oral recitation performance after the implementation of murottal-based instruction. Observational data further reveal improved student participation, greater awareness of madd segments, and increased self-correction behaviors during practice. The most substantial gains were found in identifying mad ṭabī‘ī and distinguishing madd forms associated with hamzah, while some difficulties persisted in waqf-dependent madd types (e.g., arid li-s-sukun). Overall, the study concludes that the murottal method effectively enhances students’ tajwīd competence in madd rules by providing accurate recitation models and structured repetitive practice, and it recommends targeted reinforcement for waqf-related rules and sustained practice beyond classroom sessions.